Contribution of Nitrogen Fixed by Mung Bean to the Following Wheat Crop. Issue 2 (19th January 2018) - Ilyas, Noshin; Ambreen, Fakhra; Batool, Nazima; Arshad, Muhammad; Mazhar, Roomina; Bibi, Fatima; Saeed, Maimona
ABSTRACT: Crop rotation is a supportive management practice in which legumes greatly improve the growth and yield of subsequent cereal crops, particularly wheat. In this study, effects of mung bean ( Vigna radiata ) ​ ​ on the yield and quality of grains of following wheat crop were determined. An experiment was carried out with two sets of wheat ( Triticum aestivum ) crops: one grown following mung bean ( Vigna radiata ) crop and the other grown after a fallow period. Concentrations of macronutrients, sugar, protein, amino acids, and phytohormones of wheat were determined. The grain protein concentration of wheat was improved if cultivated after mung bean, and nitrogen and other macronutrients of wheat were increased significantly. In case of phytohormone contents in the wheat crop, abscisic acid concentration showed no change, but the concentrations of gibberellin increased significantly by 41% and indole acetic acid by 30% as a result of crop rotation. Sugar content in wheat cultivated after mung bean BRM-318 showed 10% increase and wheat protein content increased by 17% and 20%, respectively. The present study demonstrated that crop rotation simulated yield and improved the nutritional value of wheat grain compared to wheat which followed the fallow period.